Pengaruh Umur terhadap Saat Muncul Kecambah dan Daya Kecambah Benih Kelapa Dalam (Cocos nucifera) - Alfred Pahala Manambangtua; Toni S. Hidayat (Jurnal Agro Industri Perkebunan, 2020)
At this time there is the development of coconut plantations in the community, so that the need for coconut seeds continues to increase, to meet these needs it needs to be supported by the provision of good quality coconut seeds, worth planting in the field and have the criteria for simultaneous sprouts and high viability. Results seedling seed growers by famer have an average of 80% germination with a seed age of 11 and 12 months. This study aims to determine the ideal age of seeds to be used as seeds that have germination speed and high viability. The research was conducted using two treatments consisting of coconut seeds aged 11 months and coconut seeds aged 12 months. Each treatment contained 100 plants so that 200 coconut seeds were used. The difference in age of coconut seeds gives significantly different results when they appear germination, the fastest results obtained on 12-month-old seeds. At the sprout power the highest yield was obtained for coconut seeds aged 12 months.